تصميم محطات القدرة المستخدمة لدفع السفن ذات الطفو الديناميكي - معروف أحمد (Tishreen University, 2019)
يندرج هذا البحث ضمن قائمة الأعمال الحثيثة التي تهدف إعداد منهجيات متطورة لتنفيذ الحسابات الهندسية التصميمية باستخدام الحواسيب الإلكترونية. يتناول البحث أحد الاتجاهات الحديثة في مجال تطوير صناعة السفن، الذي يتمثل في السفن ذات الطفو الديناميكي. في  البداية قمنا بإعطاء فكرة عامة عن مبدأ الطفو الديناميكي وتصنيفاته المختلفة وكيفية تحقيقه تكنولوجياً، ومن ثُم تم توضيح كيفية استخدام هذا المبدأ لتأمين حركة السفن التي تسير بسرعات عالية دون الحاجة إلى استهلاك كميات كبيرة من الطاقة. بعد ذلك تم إعداد المنهجيات المتعلّقة بتنفيذ الحسابات التصميمية لمجمعات الدفع (محطات القدرة) المستخدمة على هذه السفن، واستناداً إلى هذه المنهجيات تم إعداد برنامج بلغة (Visual Basic)  لتنفيذ الحسابات بواسطة  الحواسيب الإلكترونية. يستطيع هذا البرنامج معالجة الحالات المتعلّقة بتنفيذ الحسابات التصميمية كافة لمجمعات الدفع للسفن ذات الطفو الديناميكي (سفن الأجنحة التحتمائية وسفن الوسادة الهوائية)، وهو يُعتبر وسيلة للقيام بالأعمال البحثية المختلفة لدراسة تأثير العوامل التصميمية والاستثمارية على أداء هذه المجمعات وتطويرها في المستقبل. This research is one of the ongoing attempts to formulate advanced ways of aimed to preparation tidy computer aided execution accounts of the design engineering. This research can be considered as one of the modern directions in the development field of ships manufacture, which assimilate in the dynamic float ships. In the early stage we prepared general idea about principle dynamic float and different assortments and how to achieve this technology. After that we illustrate how this principle can be used to provide the movement of ships which travel at high speeds without imperative to exhaust high amounts from energy. On the other hand we prepared the tidies which tend to execution design calculations to defrayal collectors (energy stations) which can be used in these ships. Depending on these tides we prepared visual basic program language to execute accounts by electrical computers. This program can process all cases which tend to execute design calculations to defrayal collectors of dynamic float ships (under water van ships, air bolster ships). It is considered an agent to do different research connections to study the effect of design and exploitation circumstances on these collectors delivery and development in the future.